Tax Treatment of Income from Intellectual Property Rights - Lucian CERNUȘCA (CECCAR Business Review)

(untitled)
The article presents a series of theoretical and practical issues regarding the declaration and payment obligations regarding the taxation of income from intellectual property rights. Taxpayers who obtain such income owe income tax, its determination being carried out depending on the payer of the income. Along with income tax, taxpayers also have obligations under certain conditions regarding social contributions provided for by the Fiscal Code. They have the possibility to opt for determining net income in the real system, this option being mandatory for a period of two consecutive fiscal years and being considered renewed for a new period if no return to the previous system is requested.